Functional outcome of surgical management of trimalleolar fractures - Thapa, Santosh; Jha, Ranjib Kumar; Rajthala, Ashish (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Trimalleolar fractures are encountered by every orthopedic surgeon. It is very disabling if not managed properly. Trimalleolar fracture requires anatomical reduction, which can be achieved with open reduction and then internal fixation. The purpose of this study is to see the functional outcome of surgically treated trimalleolar fractures with open reduction of all fragments and internal fixation. METHODS: This is a case series of twenty-six patients diagnosed with trimalleolar fractures which were managed surgically. A preoperative x-rays and computed tomography scan were used for knowing the fracture and its pattern of such. A posterolateral approach was used for fixation of posterior malleolus and lateral malleolus in prone position and medial approach for medial malleolus fixation with tension band wiring or screws. The Olerud-Molander Ankle Score system was used at 6 months, 1 year and 2 years of follow-up to assess the functional outcome. RESULTS: The average age of patients was 46.6 years (range 20 -60 years). There were 18 (69.23%) male and 8 (30.76%) female patients. Among 26 patients, the commonest injury pattern was supination external rotation and followed by supination adduction. The average time to union and full weightbearing was 15.2 weeks (range 13–18 weeks). Average OMAS score was 70 (IQR- 30) at six month, 82 (IQR- 22.6) at 1 year and 84 (IQR- 22) at 2 years period. Overall good to excellent result was present in 92.3% of the patients. CONCLUSION: Operative treatment for trimalleolar fractures with posterior malleolus fixation results in good functional outcome. Anatomical reduction is compulsory for obtaining better functional outcome.